THE IMPORTANT METABOLIC AND MORPHOLOGICAL FEATURES OF PET/CT IMAGING IN ASBESTOS-RELATED MALIGNANT PLEURAL MESOTHELIOMA PATIENTS - Simsek, F. S. (Elsevier, 2019)
[Abstract Not Available]
CHEST Regional Congress -- JUN 27-29, 2019 -- Athens, GREECE